2018
DOI: 10.5469/neuroint.2018.13.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Cerebral Aneurysm Via Magnetic Resonance Angiography Screening: Emphasis on Legal Responsibility Increases False Positive Rate

Abstract: PurposeFalse positive diagnoses of cerebral aneurysm via magnetic resonance angiography (MRA) screening may increase unnecessary cerebral catheter angiography. The purpose of this study was to investigate the effects of medical liability on medical decision-making during radiologic interpretation.Materials and MethodsWe included 56 consecutive patients who were referred with suspected aneurysm based on MRA or computed tomography angiography (CTA) and showed no aneurysm on subsequent digital subtraction angiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…erefore, this examination was not suitable for patients with ruptured aneurysms and bleeding. Cho et al [15] and Ikawa et al [16] suggested that the lower detection rate of smaller tumors was also a drawback of MRI detection, which was consistent with this finding that CT had a higher detection rate for smaller tumors than MRI (P < 0.05). As a noninvasive examination, the application value of CT has been fully affirmed.…”
Section: Discussionsupporting
confidence: 72%
“…erefore, this examination was not suitable for patients with ruptured aneurysms and bleeding. Cho et al [15] and Ikawa et al [16] suggested that the lower detection rate of smaller tumors was also a drawback of MRI detection, which was consistent with this finding that CT had a higher detection rate for smaller tumors than MRI (P < 0.05). As a noninvasive examination, the application value of CT has been fully affirmed.…”
Section: Discussionsupporting
confidence: 72%
“…Therefore, a variable degree of anxiety is commonly observed after diagnosis, depending on the emotional response of the physician who explains the risk to the patient and recommends treatment to relieve anxiety, especially in women [ 22 ]. Recent increases in health checkups in the Korean population has meant that more young people undergo brain MRA, which results in the detection of more aneurysms [ 2 23 ]. Once detected, patients often try to seek solutions to relieve their anxiety and fear, and sometimes urge the clinician to perform invasive catheter angiography to treat the aneurysm [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many patients with unruptured intracranial aneurysm (UIA), diagnosed with aneurysm upon routine checkup, fear the risk of rupture and describe aneurysm as a “ticking time bomb” although such terms should be avoided [ 1 ]. Therefore, the care provider traditionally takes up the responsibility of explaining the actual risk of rupture and taking legal protection against any unexpected risk of adverse events, if surgery is performed, until recovery after the treatment, as the risk of surgical clipping is relatively high [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Digital subtraction angiography (DSA) remains the gold standard for diagnosis of cerebral aneurysm. Additionally, CT angiography (CTA) and magnetic resonance angiography (MRA) have also been widely proven as reliable tools for aneurysm detection (8,9). Previous researches have displayed that the prevalence of coexisting IA in patients with intracranial tumor ranges from 2.3 to 7.7% (5,10), of which, meningioma and pituitary adenoma were considered as the most frequent brain tumors in relation to higher occurrence of cerebral aneurysm (10,11), predominantly unruptured aneurysms.…”
Section: Introductionmentioning
confidence: 99%